Synthesis and evaluation of phosphoramidate and phosphorothioamidate analogues of amiprophos methyl as potential antimalarial agents - BELL, ANGUS; DEMPSEY, ENDA (Elsevier, 2011)
A series of phosphoramidate and phosphorothioamidate compounds based on the lead antitubulin herbicidal agents amiprophos methyl (APM) and butamifos were synthesised and evaluated for antimalarial activity. Of these compounds, phosphorothioamidates were more active than their oxo congeners and the nature of both aryl and amido substituents influenced the desired activity. The most active compound was 46, O-ethyl-O-(2-methyl-4-nitrophenyl)-N-cyclopentyl phosphorothioamidate, which was more effective than the lead compound.
PUBLISHED
Keywords: Immunology; phosphoramidate